The teaching of EFL reading at a university level: Teachers' and students' perceptions - Moh Junaidi; Mutmainnah Mustofa; M Faruq Ubaidillah; Huan Yik Lee (International Journal of Education and Learning, 2023)
This study investigated the teaching of EFL reading at a university level from teacher’s and students’ perspectives. It delved into how the participating lecturer conducted the teaching of reading. Moreover, it shared the difficulties of teaching reading and the difficulties of students in reading. In this research, the researchers used a case study. The researchers used observation and interviews to collect the data. The participants of this study are one lecturer and three students situated in a private Islamic university in Malang, Indonesia. The recruited lecturer has been teaching reading for more than 10 years. Meanwhile, the recruited students were selected because they were close to the researchers and easy to access. The findings suggest that the teaching of reading was done by making a group discussion and cooperative learning such as Think-Pair-Share and Jigsaw. Besides, the minimal access to high-quality books for students’ reading tasks is one of the difficulties in the teaching of reading. Students also found it difficult to read difficult words. Mostly, they skipped the words and struggled to look for the text's main ideas and topic sentences. Finally, based on the result of the study, it is suggested that English lecturers should use appropriate reading books and techniques, select other supplementary materials, and vary the teaching activities. Future researchers are urged to conduct more intensive research in the teaching of reading in different contexts.